Cardiovascular Health and Risk Factors Among Adult Study Participants: Insights from Sociodemographic Characteristics and Health Behaviors - Odeigah, Louis O.; Agede, Olalekan A.; Ogunjemilua, Sunday B.; Oyedepo, Dapo S.; Okoro, Peace N.; Sanni, Nasiru (Universitas Brawijaya, 2025)
Background: Cardiovascular diseasesconstitute a significant global health challenge, necessitating a comprehensive understanding of their risk factors. This study explores the interplay between sociodemographic characteristics, health behaviors, and cardiovascular health among adult participants. Aim: The study aims to assess the cardiovascular health status and risk factors in adults, considering sociodemographic characteristics and health behaviors. Methods: In the Inter-University Consortium for Political and Social Research Study (ICPSR146521), data that had been gathered prospectively were used to assess the prevalence of metabolic syndrome, its risk factors, and the linked lifestyle in adult Myanmar inhabitants. Results: The study found that age was significantly associated with cardiovascular health, with an increase in age correlating with elevated risk. While gender was not a significant predictor, marital status and occupation played roles in shaping cardiovascular health outcomes. Smoking and sedentary lifestyles were identified as substantial risk factors, while physical exercise and healthier dietary habits demonstrated protective effects. Regression analysis further underscored the influence of BMI, age, and total cholesterol on cardiovascular health. Conclusion: This study provides critical insights into the complex interplay between sociodemographic characteristics, health behaviors, and cardiovascular health among adults. The findings emphasize the significance of age, smoking, physical activity, and dietary choices in shaping cardiovascular risk. Tailored interventions and public health strategies that consider these factors can enhance cardiovascular diseases prevention and management efforts, ultimately contributing to a reduction in the global burden of cardiovascular diseases.